Religious preferences as a factor of influence on the outcome of election campaigns in MODERN RUSSIA - O. E. Grishin; O. S. Stepuro (Проблемы постсоветского пространства)
The article deals with the religious preferences of citizens influencing the electoral choice of religious citizens. Reveals some of the means and methods of influence on voters by religious organizations. The attention on the actions of the Russian Orthodox Church. Showcased religious sympathies of the citizens of Russia to some politicians.